Dependable wireless real-time communications for open environments - Bartolomeu, Paulo Jorge de Campos (2018)
Wireless communication technologies have become widely adopted, appearing in heterogeneous applications ranging from tracking victims, responders and equipments in disaster scenarios to machine health monitoring in networked manufacturing systems. Very often, applications demand a strictly bounded timing response, which, in distributed systems, is generally highly dependent on the performance of the underlying communication technology. These systems are said to have real-time timeliness requirements since data communication must be conducted within predefined temporal bounds, whose unfulfillment may compromise the correct behavior of the system and cause economic losses or endanger human lives. The potential adoption of wireless technologies for an increasingly broad range of application scenarios has made the operational requirements more complex and heterogeneous than before for wired technologies. On par with this trend, there is an increasing demand for the provision of cost-effective distributed systems with improved deployment, maintenance and adaptation features. These systems tend to require operational flexibility, which can only be ensured if the underlying communication technology provides both time and event triggered data transmission services while supporting on-line, on-the-fly parameter modification. Generally, wireless enabled applications have deployment requirements that can only be addressed through the use of batteries and/or energy harvesting mechanisms for power supply. These applications usually have stringent autonomy requirements and demand a small form factor, which hinders the use of large batteries. As the communication support may represent a significant part of the energy requirements of a station, the use of power-hungry technologies is not adequate. Hence, in such applications, low-range technologies have been widely adopted. In fact, although low range technologies provide smaller data rates, they spend just a fraction of the energy of their higher-power counterparts. The timeliness requirements of data communications, in general, can be met by ensuring the availability of the medium for any station initiating a transmission. In controlled (close) environments this can be guaranteed, as there is a strict regulation of which stations are installed in the area and for which purpose. Nevertheless, in open environments, this is hard to control because no a priori abstract knowledge is available of which stations and technologies may contend for the medium at any given instant. Hence, the support of wireless real-time communications in unmanaged scenarios is a highly challenging task. Wireless low-power technologies have been the focus of a large research effort, for example, in the Wireless Sensor Network domain. Although bringing extended autonomy to battery powered stations, such technologies are known to be negatively influenced by similar technologies contending for the medium and, especially, by technologies using higher power transmissions over the same frequency bands. A frequency band that is becoming increasingly crowded with competing technologies is the 2.4 GHz Industrial, Scientific and Medical band, encompassing, for example, Bluetooth and ZigBee, two lowpower communication standards which are the base of several real-time protocols. Although these technologies employ mechanisms to improve their coexistence, they are still vulnerable to transmissions from uncoordinated stations with similar technologies or to higher power technologies such as Wi- Fi, which hinders the support of wireless dependable real-time communications in open environments. The Wireless Flexible Time-Triggered Protocol (WFTT) is a master/multi-slave protocol that builds on the flexibility and timeliness provided by the FTT paradigm and on the deterministic medium capture and maintenance provided by the bandjacking technique. This dissertation presents the WFTT protocol and argues that it allows supporting wireless real-time communication services with high dependability requirements in open environments where multiple contention-based technologies may dispute the medium access. Besides, it claims that it is feasible to provide flexible and timely wireless communications at the same time in open environments. The WFTT protocol was inspired on the FTT paradigm, from which higher layer services such as, for example, admission control has been ported. After realizing that bandjacking was an effective technique to ensure the medium access and maintenance in open environments crowded with contention-based communication technologies, it was recognized that the mechanism could be used to devise a wireless medium access protocol that could bring the features offered by the FTT paradigm to the wireless domain. The performance of the WFTT protocol is reported in this dissertation with a description of the implemented devices, the test-bed and a discussion of the obtained results.